Peripheral Vascular Disease “A Spectrum” - Naeem Zia, Naeem Zia; Mohammad Hanif, Mohammad Hanif; Umar Farooq, Umar Farooq; Naveed Malik, Naveed Malik; Umar Farooq Niazi, Umar Farooq Niazi; Mohammad Mussadiq Khan, Mohammad Mussadiq Khan (Journal of Rawalpindi Medical College, 2007)
Background: To observe the spectrum of peripheral vascular disease presenting in a tertiary care hospital. Method: This observational, descriptive study was carried out in Surgical Unit –I at Holy Family Hospital, Rawalpindi over a period of two years. All the patients presenting with peripheral vascular disorders excluding acute vascular trauma patients, diabetics and varicose veins patients were included in the study. Results: A total of 49 patients presented to the hospital. The male to female ratio was 2:1.The average age of presentation was 50.2 years. About 35% patients presented with occlusive disease, 18% with autoimmune disease and 14% with embolism. The less common causes of peripheral vascular disorders included femoral pseudoaneurysms in 8% patients and true aneurysms of iliac, popliteal and subclavian arteries in 12% patients. Bilateral gangrene of both lower limbs was seen in 4% patients. Conclusion: Peripheral vascular disease is commoner in males and is mostly seen in the sixth decade of life. Atherosclerotic occlusive disease is the commonest cause of peripheral vascular disease followed by vasculitis, embolisms and aneurysms.